NUTRITION OF FREQUENTLY ILL CHILDREN IN KINDEGARTENS - Imamova Akida Obidjon qizi; Khobiljonova Shakhnoza Rustam qizi (The Conference Hub, 2025)
Frequently ill children in preschool settings face unique nutritional challenges that can impact their immune function and overall health. This article examines the nutritional status of these children, identifies common deficiencies, and proposes strategies to enhance their dietary intake. A comprehensive review of existing literature and observational studies was conducted to assess the correlation between nutrition and illness frequency among preschoolers. Findings indicate that inadequate nutrition, particularly deficiencies in essential nutrients, contributes to increased susceptibility to infections. Implementing balanced diets rich in fruits, vegetables, lean proteins, and whole grains, along with educational initiatives for caregivers, can significantly improve health outcomes for this vulnerable population.
Keywords: frequently ill children, preschool nutrition, immune function, dietary deficiencies, health interventions